Impacts of heart rate variability on post-traumatic stress disorder risks after physical injuries: amplification with childhood abuse histories - Jeon, Ji Hyeon; Kim, Ju-Wan; Kang, Hee-Ju; Jang, Hyunseok; Kim, Jung-Chul; Lee, Ju-Yeon; Kim, Sung-Wan; Shin, Il-Seon; Kim, Jae-Min (Frontiers in Psychiatry, 2024)
IntroductionThis study examined the moderating effects of childhood abuse histories on the associations between low frequency (LF) and high frequency (HF) components of heart rate variability (HRV) and the development of post-traumatic stress disorder (PTSD).MethodsParticipants with physical injuries were recruited from a trauma center and followed for two years. Baseline assessments included LF, HF, and childhood abuse histories, assessed using the Nemesis Childhood Trauma Interview. Socio-demographic and clinical covariates were obtained. PTSD diagnoses were made at 3, 6, 12, and 24 months post-injury using the Clinician-Administered PTSD Scale for DSM-5. Logistic regression analyses assessed the associations.ResultsAmong 538 participants, 58 (10.8%) developed PTSD during the study period. A significant interaction was found: lower LF/HF were significantly associated with PTSD in patients with childhood abuse histories, but not in those without.ConclusionChildhood abuse history significantly moderates the relationship between LF-HF HRV components and PTSD development, suggesting that childhood adversities amplify the risk. These findings support the importance of screening for childhood abuse histories and monitoring HRV in physically injured patients as part of the assessment process.